The tidal freshwater river zone: Physical properties and biogeochemical contribution to estuarine hypoxia and acidification - The "hydrologic switch". (5th May 2022) - O'Connor, John A.; Erler, Dirk V.; Ferguson, Angus; Maher, Damien T.
Abstract: The river's role as the aquatic continuum, transporting and transforming terrestrial material in transit to sea, has long been appreciated. Along this aquatic continuum lies an enigmatic river stretch known as the tidal freshwater zone (TFZ). Because it oscillates along the daily tidal cycle, yet records no salinity, TFZs are often overlooked or sporadically studied. Additionally, research efforts into TFZs have been disproportionately focused on the intertidal zone rather than the subtidal zone. The limited studies to date do, however, highlight the subtidal TFZ's importance in both the removal and transformation of terrestrial material before exchange at sea, and, as both a primary production and respiration hotspot. The shifts between biogeochemical activity within the TFZ vary in a semi-predictable manner based on hydrologic state. Presented here is a conceptual model, defining the TFZ as inseparable from the traditionally studied estuary by reviewing the relevant literature. The TFZ acts as a "fluidized bed reactor" which depends on marine and aquatic material delivery and tidally prolonged retention times. Subsequently, TFZ biogeochemical byproducts affect the saline estuarine reach's chemistry, water quality, and ecology. Specifically, TFZ biogeochemistry contributes significantly to episodic acidification and deoxygenation in the saline reaches, due to a hydrologic switch. Therefore, conceptualizing the TFZ and estuary as a single entity oscillating jointly between river and ocean dominated forces, within the framework of the pulse-shunt concept, developed in low order stream networks, is most apt. TFZ ecological and hydrological restoration efforts, like those occurring in the traditional estuary, will be needed to mitigate hydrologic switch events in the future. Highlights: Global trends in tidal freshwater zone (TFZ) biogeochemistry are reviewed. TFZs provide significant substrate to facilitate estuarine hypoxia and acidification. Extent of impairment varies as a function of hydrologic connectivity. Changes in biogeochemical processes in TFZs due to sea level rise are also discussed. Conceptual models to design future research directions are described at length.